A legal study on elder abuse in Malaysia / Nini Sabarina Ismail, Noor Farhah Mustaffa and Nurulartiah Haris - Ismail, Nini Sabarina; Mustaffa, Noor Farhah; Haris, Nurulartiah (2011)
This research paper describes the nature and legal perspective of elder abuse. This paper with a view of establishing the meaning of elder abuse in United States of America, Japan, Singapore and in Malaysia as well. This particular paper also focus on the nature of elder abuse with regards to its types and the sources of the abuse itself. Besides that, this paper includes the laws that deals with elder abuse issue in each country and to what extent the respective laws are efficient in curbing that particular issue. A comparative analysis is drawn between the three countries including Malaysia in determining whether elder abuse is categorized as crime in each country. In addition, when it is recognized as crime in each country, the responsible authorities have several approaches in tackling with this problem. The recommendations need to be disseminated as to improve the effect of elder abuse. Thus, greater awareness would be the crucial and essential aspect about elder abuse and ways to prevent circumstances resulted from the abuse.